Performance review results: a key moment for employees and managers in the Algerian company - Naga, Nahla (Management and Entrepreneurship: Trends of Development, 2023)
The economic environment in Algeria is constantly changing, presenting businesses with crucial challenges. To maintain  their competitiveness, these businesses now recognize the vital importance of enhancing the performance of their human resources. Measuring, assessing, and communicating employee performance outcomes are essential steps to ensure the success and longevity of the company. In this context, a study was conducted within an Algerian leather company to evaluate the impact of transparent communication of assessment results on performance improvement. The initial hypothesis suggests that non-confidential communication of results promotes a qualitative enhancement in performance by highlighting each employee's specific skills and areas for improvement. A methodology was established to collect and interpret data, enabling a deeper understanding of the effects of this transparent communication on employee motivation, engagement, and perception of evaluations. By utilizing questionnaires, we collected essential insights from employees and pertinent managers, enabling us to gain a more comprehensive understanding of how transparently communicating assessment results influences their motivation, engagement, and perception of the evaluation process. Our research discovered that employees who perceive their supervisors as just and impartial tend to experience higher job satisfaction and greater motivation to excel in their roles. This phenomenon is attributed to the fact that managers who uphold fairness and equity foster a positive workplace atmosphere, cultivating a sense of worth and assistance among employees. Additionally, they establish well-defined expectations and objectives, enabling employees to remain focused and attain their utmost potential. The process of performance appraisal holds significant potential for enhancing both employee and organizational performance. JEL Classification: M1, M12, M0.